Modified human skin cell isolation protocol and its influence on keratinocyte and melanocyte culture - Zhi Liu; Shunxin Jin; Dapeng Cheng; Hao Chen; Yuxiang Wang; Chao Ji; Zhenzhen Yan; Xiao Fang; Shichu Xiao; Xinling Bi (Regenerative Therapy)
Introduction: With the increasing emphasis on the use of nonanimal ingredients in clinical care, studies have proposed the use of TrypLE™ as an alternative to trypsin. However, previous research has reported insufficient cell yield and viability when using TrypLE to isolate skin cells compared to the dispase/trypsin-EDTA method. This study aimed to propose an improved method for increasing the yield and viability of cells isolated by TrypLE and to evaluate isolated keratinocytes and melanocytes. Methods: Foreskin tissues were isolated to keratinocytes and melanocytes using the trypsin-EDTA protocol and our modified TrypLE protocol. The yield and viability of freshly isolated cells were compared, the epidermal residue after cell suspension filtration was analyzed histologically, and the expression of cytokeratin 14 (CK14) and Melan-A was detected by flow cytometry. After cultivation, keratinocytes and melanocytes were further examined for marker expression and proliferation. A coculture model of melanocytes and HaCaT cells was used to evaluate melanin transfer. Results: The yield, viability of total cells and expression of the keratinocyte marker CK14 were similar for freshly isolated cells from both protocols. No differences were observed in the histologic analysis of epidermal residues. Moreover, no differences in keratinocyte marker expression or melanocyte melanin transfer function were observed after culture. However, melanocytes generated using the TrypLE protocol exhibited increased Melan-A expression and proliferation in culture. Conclusion: Our TrypLE protocol not only solved the problems of insufficient cell yield and viability in previous studies but also preserved normal cell morphology and function, which enables the clinical treatment of depigmentation diseases.